Reinterpreting ekatvādīn in Mūlamadhyamakakārikā 19:4 A Grammatical and Ontological Analysis - Kang, Jiayue (Mahachula Academic Journal, 2025)
This article offers a focused re-examination of the term ekatvādīn in MMK 19:4 of Nāgārjuna’s Kālaparīkṣā (Chapter 19 of the Mūlamadhyamakakārikā), arguing that its grammatical form and ontological function have been systematically underappreciated in both classical and modern scholarship. While commentators commonly gloss ekatvādīn numerically as “unity, duality and plurality,” treating it as a loose analogue to temporal divisions, this reading neither accounts for the masculine plural ending -ādīn attached to the neuter abstract noun ekatva, nor does it explain its precise role in Nāgārjuna’s extension of the critique of time to space and identity. Through close Sanskrit analysis and engagement with Bhāvaviveka, Candrakīrti, Tsongkhapa, as well as modern interpreters such as Kalupahana, Garfield, and Siderits & Katsura, the article proposes a reinterpretation of ekatvādīn as a relational triad, “Identity – Neither Identity nor Difference – Difference” (ekatvābhedābheda), rather than a merely numerical series. This grammatical anomaly is read as a deliberate device that destabilises reified identity just as Kālaparīkṣā destabilises temporal phases. The analysis shows that ekatvādīn functions as a pivot linking temporal, spatial and identity schemata, thereby revealing them as interdependent conceptual constructions lacking inherent existence (svabhāva). In doing so, the article seeks to contribute to ongoing discussions that treat Nāgārjuna not merely as a logician of emptiness but as a subtle reader of language, whose grammatical choices are integral to the deconstruction of substantiality.